Development and validation of a necroptosis-related gene prognostic score to predict prognosis and efficiency of immunotherapy in gastric cancer - Xia, Yan; Zhang, Rongzheng; Wang, Mingzhu; Li, Jiaqi; Dong, Jianming; He, Kaitong; Guo, Ting; Ju, Xiaomei; Ru, Jiaqiu; Zhang, Shuyun; Sun, Yihua (Frontiers in Immunology, 2022)
Necroptosis is a new type of regulated cell death that is intimately associated with a variety of tumors. However, how necroptosis affects the identification of gastric cancer (GC) remains unclear. Here we seek to find new potential necroptosis-related biomarkers to predict GC prognosis and immunotherapy efficacy. We used Cox analysis to obtain shared prognostic markers related to necroptosis from five datasets (TCGA and four GEO datasets). Then, a necroptosis-related gene prognostic score (NRGPS) system was constructed using LASSO Cox regression, NRGPS consisting of three necroptosis-related mRNAs (AXL, RAI14, and NOX4) was identified, 31 pairs of GC and adjacent normal tissues from the Second Hospital of Harbin Medical University were collected and Real-Time Quantitative PCR (RT-qPCR) was used to detect the relative expression levels of the three necroptosis-related mRNAs, using the GSE84437, GSE26901, GSE62254 and GSE15459 datasets from the GEO were used for external validation. Kaplan–Meier analysis and time-dependent ROC curve analysis were used to evaluate the predictive value of NRGPS system. In this study, The high-NRGPS group had significantly lower the overall survival (OS) than the low-NRGPS group. Cox regression analyses showed that NRGPS was an independent prognostic variable. Tumor-mutation-burden (TMB), tumor microenvironment (TME), microsatellite instability (MSI), and Tumor Immune Dysfunction and Exclusion (TIDE) scoring were used as predictors of the immunotherapy response. The high-NRGPS group was characterized by a cancer-friendly immune microenvironment, a high TIDE score, and a low TMB, a low MSI all of which consistently demonstrated that the problems observed in the high-NRGPS group are associated with immune escape in GC. The combination of three candidate genes may be an effective method for diagnostic assessment of GC prognosis and immunotherapy efficacy.